1997
DOI: 10.1038/sj.bjp.0701401
|View full text |Cite
|
Sign up to set email alerts
|

An endogenous A2B adenosine receptor coupled to cyclic AMP generation in human embryonic kidney (HEK 293) cells

Abstract: 1 Cyclic AMP generation by adenosine analogues was examined in human embryonic kidney (HEK 293) cells by use of a [ 3 H]-adenine pre-labelling methodology. 2 Adenosine analogues showed the following rank order of potency (pD 2 value): 5'-N-ethylcarboxamidoadenosine (NECA, 5.24)42-chloroadenosine (4.41) 5 adenosine (4.19)=N 6 -(2-(4-aminophenyl)-ethylamino)adenosine (APNEA, 4.11). The A 2A -selective agonist CGS21680 failed to elicit a signi®cant stimulation of cyclic AMP generation at concentrations below 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 16 publications
2
60
0
Order By: Relevance
“…3). Despite the fact that several studies had previously suggested the existence of endogenous A2b-R on HEK-293 cells (Cooper et al 1997, Gao et al 1999, Linden et al 1999, the density of this receptor appeared to be too low to contribute to calcium activity of adenosine in these cells. To our knowledge, there is no data about the expression of A3-R on HEK-293 cells.…”
Section: Endogenous Adenosine Receptorsmentioning
confidence: 88%
“…3). Despite the fact that several studies had previously suggested the existence of endogenous A2b-R on HEK-293 cells (Cooper et al 1997, Gao et al 1999, Linden et al 1999, the density of this receptor appeared to be too low to contribute to calcium activity of adenosine in these cells. To our knowledge, there is no data about the expression of A3-R on HEK-293 cells.…”
Section: Endogenous Adenosine Receptorsmentioning
confidence: 88%
“…Also, SCH 58261 weakly antagonized both adenosine and CGS21680 responses but was ineffective against 2Cl-IB-MECA. Although VUF5574 completely antagonized the adenosine and CGS21680 dose-response functions in the double-recombinant hA3/G␣q-i3/293 cells, we cannot yet rule out the possibility that simultaneous activation of endogenous cAMP-linked A2B receptors (Cooper et al, 1997) could influence the magnitude of the A3-mediated calcium signals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ADP exhibited only P2Y 14 -R-dependent activity at very high concentrations relative to those necessary for agonist effects of UDP. A potential explanation of the stimulatory effect of ADP in both wild-type and P2Y 14 -HEK293 cells is that ec- toenzymes convert ADP to adenosine, which in turn activates an endogenous A 2B adenosine receptor known to be present on HEK293 cells (Cooper et al, 1997;Mundell et al, 1999).…”
Section: Resultsmentioning
confidence: 99%